Crystal structures explain functional differences in the two actin depolymerization factors of the Malaria parasite - Singh, Bishal; Sattler, Julia M.; Chatterjee, Moon; Huttu, Jani; Schüler, Herwig; Kursula, Inari (The journal of biological chemistry, 2011)
Apicomplexan parasites, such as the malaria-causing Plasmodium, utilize an actin-based motor for motility and host cell invasion. The actin filaments of these parasites are unusually short, and actin polymerization is under strict control of a small set of regulatory proteins, which are poorly conserved with their mammalian orthologs. Actin depolymerization factors (ADFs) are among the most important actin regulators, affecting the rates of filament turnover in a multifaceted manner. Plasmodium has two ADFs that display low sequence homology with each other and with the higher eukaryotic family members. Here, we show that ADF2, like canonical ADF proteins but unlike ADF1, binds to both globular and filamentous actin, severing filaments and inducing nucleotide exchange on the actin monomer. The crystal structure of Plasmodium ADF1 shows major differences from the ADF consensus, explaining the lack of F-actin binding. Plasmodium ADF2 structurally resembles the canonical members of the ADF/cofilin family.